The role of gaze and viewpoint in a rapid serial visual presentation paradigm - Goh, Benjamin Kiat (2019)
This study investigates the performance of human face categorization. Existing research has determined two fundamental, yet distinct processes in understanding human face perception. These processes in study are face categorization and recognition. While there have been significant advances in understanding human face recognition, little study has been done to understand the processes involved in human face categorization by humans. Our interest lies in how the direction of the gaze and the head viewpoints of individuals can affect the categorization speed. Therefore, in our study, we conducted a 2 x 3 within-subject analysis of variance (ANOVA) using 20 participants (M = 22.5, SD = 1.47) to explore the different elements contributing to face categorization. The Rapid Serial Visual Presentation paradigm was used, with a high presentation speed of 90ms for each image. Our results demonstrated that the reaction time is significantly faster for faces with direct gaze (47ms faster), or frontal viewpoint (37ms faster), or faces showing both direct gaze and frontal viewpoint (60ms faster). Thus, we established the importance of the direction of gaze and viewpoint in the categorization of human faces at a high presentation speed.